"Achievement unlocked!" - The impact of digital achievements as a gamification element on motivation and performance. (August 2019) - Groening, Christopher; Binnewies, Carmen
Abstract: Gamification experiences further growth in our society with broad practical implications of game design elements in applications, activities, and services. In our study, we focus on one single element in the form of digital achievements, one cornerstone of gamification, to gain unconfounded insights into the effects and working mechanisms of digital achievements. In a controlled experimental environment we investigate their impact on motivation and performance. Three research questions were investigated, first, if achievements are effective in enhancing motivation and performance, second, how achievements need to be designed to be effective, and third, if achievements' underlying working mechanisms resemble classical goal-setting. In three experiments, a total of 245 participants worked on different cognitive tasks. We experimentally manipulated several aspects of achievements, such as quantity and difficulty. We also compared achievements directly with classical goal-setting instructions. Results showed that achievements enhanced performance. Achievements also improved motivation, however only regarding persistence, not self-reported interest and enjoyment. The effectiveness of achievements was highly dependent on the design. Results suggest utilizing achievements with high difficulty and in low quantity. Results also support our assumption that achievements provide a direct goal-setting function. We conclude that achievements do benefit motivation and performance if designed properly. Highlights: Achievements improve performance. Achievements improve motivation regarding persistence but not self-reports. Achievements are more effective when designed in high difficulty and low quantity. Achievements resemble classical goal-setting regarding their working mechanisms. Achievements improve performance more than goal-setting over time.